2020
DOI: 10.2174/1570179417666191227115207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Piperazine Substituted Chalcone Sulphonamides as Antibacterial Agents

Abstract: Background: Infection is a global threat to human health, and there is an urgent need to develop new effective antibacterial drugs to treat bacterial infections. Objective: To study the antibacterial activity of piperazine substituted chalcone sulphonamides. Materials and Methods: A series of novel piperazine substituted chalcone sulphonamides have been prepared, and in vitro antibacterial activity against Staphylococcus aureus, Bacillus subtilis and Escherichia coli strains were evaluated. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In another study using monomeric chalcone compounds, there was higher antibacterial activity in Gram-positive bacteria than the Gram-negative bacteria [ 59 ]. A screening method of chalcone derivatives against S. aureus , B. subtilis , E. coli , and P. aeruginosa showed increased lipophilic area, and the smaller molecular size of chalcones increased their antimicrobial activity [ 60 ].…”
Section: Basic Fragmentation Pathways Of Chalcones Are Obtained By Lo...mentioning
confidence: 99%
“…In another study using monomeric chalcone compounds, there was higher antibacterial activity in Gram-positive bacteria than the Gram-negative bacteria [ 59 ]. A screening method of chalcone derivatives against S. aureus , B. subtilis , E. coli , and P. aeruginosa showed increased lipophilic area, and the smaller molecular size of chalcones increased their antimicrobial activity [ 60 ].…”
Section: Basic Fragmentation Pathways Of Chalcones Are Obtained By Lo...mentioning
confidence: 99%
“…[1] They are also important intermediates for the production of a variety of biologically potent heterocyclic compounds. [2][3][4] Wide biological profile of chalcones containing a heterocyclic moiety include antiproliferative, [5] anticancer, [6] antioxidant, [7] antiviral, [8] antituberculosis, [9] antibacterial, [10] antifungal, [11] antihypertensive, [12] etc. 2,3-dihydrobenzofuran is an organic compound in which a dihydrofuran ring is fused with benzene.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamides are an imperative class of organic compounds which are an unremitting fascination for medicinal chemists and researchers due to their rich bioactive profile. A brief literature review has demonstrated that several sulfonamide derivatives have been found to be the potent inhibitors of purinergic receptors. Gefapixant, a selective inhibitor of P2X3 receptor, is a sulfonamide derivative that is a promising remedy for chronic cough …”
Section: Introductionmentioning
confidence: 99%